The West's contribution to the modernization of China—: Opportunities and limits - Wolfgang Klenner (Intereconomics, 1980)
It is China's intention to draw level with world standards in crucial areas of production, services and infrastructure by the end of the twentieth century. The Chinese development objectives are creating an interest in close cooperation with the Western industrialized nations wishing to contribute to the modernization of China? What limits have to be kept in view?
Keywords: 330; China